Optimisme Anak Didik Lembaga Pembinaan Khusus Anak (LPKA) Bandung Menuju Masa Reentry - Eka Fauziyya Zulnida; Ghinaya Ummul Mukminin (JURNAL PSIKOLOGI INSIGHT, 2023)
This study aims to describe optimism and identify factors that influence optimism of young inmates in Juvenile Hall Bandung. Optimism is a person's positive expectation of his future, while reentryis a process of returning to society for young inmates. Participants in this study are two children with drug case and violation of order case. This study uses qualitative approach with case study method. Data was collected using in depth interview technique and case study data analized by using thematic analysis. These results show that there are two approaches in the positive expectations of young inmates about their future. There are the expectations related to career and expectations related to behavioral changes. Then the result also indicaate the factors that influence the optimism are: self efficacy, self acceptance, self evaluation, self image, religious coping, intrinsic and extrinsic motivation, and emotional regulation.